Increased preoperative greater tuberosity angle does not affect patient-reported outcomes postarthroscopic rotator cuff repair - Cheryl Gatot, MBBS; Merrill Lee, MBBS, MRCS (Edin); Jerry Yongqiang Chen, MBBS, MRCS (Edin), MMED (Ortho), FRCSEd (Orth), FAMS; Benjamin Ang Fu Hong, MBBS, MRCS (Edin), MMED (Ortho), FRCSEd (Orth), FAMS; Denny Lie Tijauw Tjoen, MBBS, FRCS (Edin), FAMS (JSES International, 2021)
Background: The greater tuberosity angle (GTA) is a newly described radiological parameter identified in a 2018 study by Cunningham et al that sought to investigate the effect of GT morphology on cuff tears. Increased GTA has been conceptualized to affect rotator cuff pathology through both extrinsic and intrinsic mechanisms. GTA > 70° was highly predictive of a degenerative rotator cuff tear. This study seeks to examine if increased GTA predicts for worse functional outcomes 2 years postoperatively after arthroscopic rotator cuff repair. Methods: Between May 2010 and December 2016, 169 patients who underwent arthroscopic rotator cuff repair with subacromial decompression were included in this study. GTA was measured on preoperative radiographs. These patients were evaluated preoperatively and at 3 months, 6 months, 1 year, and 2 years postoperatively. Outcomes were assessed with the Visual Analog Scale Pain score, Constant Shoulder Score, and the Oxford Shoulder Score. Power analysis was performed based on the minimal clinically important difference of the Constant Shoulder Score. Statistical analysis was performed by dividing patients into two groups based on GTA: 1) ≤ 70 (control GTA); and 2) >70 (increased GTA) and comparisons were made between the 2 groups. Results: The patients’ demographics were comparable between both groups. All 169 patients had statistically significant improvements in all functional scores at 2 years postoperatively. There were no statistically significant differences between the two groups of patients in Visual Analog Scale and functional scores at 3 months, 6 months, 1 year, and 2 year postoperatively. The changes in functional scores from their preoperative baseline were also tabulated, and there were no statistically significant differences between the 2 groups. Finally, there was no significant correlation between GTA with CSS or Oxford Shoulder Score at 2 years follow-up. Conclusion: This study represents the largest single series available investigating the influence of GTA on midterm functional outcomes after arthroscopic rotator cuff repair. Although GTA remains a reliable radiographic predictor of rotator cuff tears, the authors conclude that increased GTA does not negatively influence midterm functional outcomes. As there is also no statistical significance between increased GTA vs. control in relative functional gain 2 years postoperatively, corrective tuberoplasty may not be mandatory during arthroscopic repair of cuff tears. Standard arthroscopic double-row rotator cuff repair with subacromial decompression can still be offered as a suitable treatment option.